ASPECTS CONCERNING THE BEHAVIOUR OF BUILDINGS DURING TIME - Cornel Arsene (Agricultura)
Monitoring the way constructions behave over time is a corollary of the construction activity, constituting an obligation of the builder in relation to the works he has carried out and has been practiced, in various forms, since the beginning of construction. This paper presents aspects and manifestations that appeared in the process of monitoring a construction that was "disadvantaged" from the start due to the nature of the foundation land.